The System of Conjugation of Old Armenian according to G. Jahukyan - PARONYAN, NAIRA (Bulletin of Yerevan University B: Philology, 2021)
According to G. Jahukyan Old Armenian has preserved the main peculiarities of the Indo-European type. For the Indo-European language- the bases restore two types of conjugation: athematic and thematic. The Old Armenian System of Conjugation appears in two main types: bases on the vowels ո, ա, ի, ու (thematic types) and the bases on sonatas ն, ր, ղ (athematic). Jahukyan considers, that in some cases there are no special difficulties in establishing the belonging to this or that type ofconjugation. Thus, it is very easy to establish the types of word conjugations, ending in– ի, -(ը)ր –(ը)ղ. According to him, difficulties arise for the words which end in ո, ի/ա,ի, ու, ն. In these cases it is possible to establish the following rules: 1) the rule of the quantity of the syllables 2) the rule of assimilation impact 3) the rule of dissimilation impact 4) the rule of semantic grouping 5) the rule of functional differentiation 6) the rule of domination in case of crossing 7) the rule of doublets in case of crossing.
Keywords: system of conjugation, thematic, athematic, feminine rhyme, sonorous rhyme, suppletive base, syllable quantity, assimilation, dissimilation, crossing